Multimode, Aperiodic Terahertz Surface-Emitting Laser Resonators - Simone Biasco (Photonics, 2016)
Quasi-crystal structures are conventionally built following deterministic generation rules although they do not present a full spatial periodicity. If used as laser resonators, they open up intriguing design possibilities that are simply not possible in conventional periodic photonic crystals: the distinction between symmetric (vertically radiative but low quality factor Q) and anti-symmetric (non-radiative, high Q) modes is indeed here fully overcome, offering a concrete perspective of highly efficient vertical emitting resonators. We here exploit electrically pumped terahertz quantum cascade heterostructures to devise two-dimensional seven-fold quasi-crystal resonators, exploiting rotational order or irregularly distributed defects. By lithographically tuning the lattice quasi-periodicity and/or the hole radius of the imprinted patterns, efficient multimode surface emission with a rich sequence of spectral lines distributed over a 2.9–3.4 THz bandwidth was reached. We demonstrated multicolor emission with 67 mW of peak optical power, slope efficiencies up to ≈70 mW/A, 0.14% wall plug efficiencies and beam profile results of the rich quasi-crystal Fourier spectrum that, in the case of larger rotational order, can reach very low divergence.